Composition of fruit-feeding butterflies (lepidoptera:nymphalidae) in a peat swamp Forest, Kota Samarahan, Sarawak - Christharina S. Gintoron; Fatimah Abang (Pusat Sistematik Serangga ,UKM, 2014)

(untitled)
A total of 104 individuals of fruit-feeding butterflies representing 24 species and 13 genera were recorded in a 60 continuous days of sampling (26 July to 23 September 2007), in a peat swamp forest in Kota Samarahan, Sarawak. Four subfamilies of Family: Nymphalidae were listed which includes Charaxinae, Morph inae, Nymphalinae and Satyrinae. Ten fruit baited-traps were utilized in this study, and were set-up in both ground and canopy strata by applying Single-Rope Technique in five different individual trees. An average of two individuals per day was recorded with 33.33% of the total samples are represented by Nymphalinae. Known to be strong and rapid fliers, this group of nymphalids is associated with increased light intensity which was observed with the less pronounced canopy at the study area. All recorded nymphalids were also designated with rank in order to assess the rank-abundance distribution of these butterflies. Overall, nymphalids with wider range of geographical distribution were less abundant and vice versa in the present study. One endemic to Borneo nymphalid species which is Mycalesis amoena was sampled in this study.